Ovule Gene Expression Analysis in Sexual and Aposporous Apomictic Hypericum perforatum L. (Hypericaceae) Accessions - Galla, Giulio; Basso, Andrea; Grisan, Simone; Bellucci, Michele; Pupilli, Fulvio; Barcaccia, Gianni (Frontiers in Plant Science, 2019)
Hypericum perforatum L. (2n=4x=32) is an attractive model system for the study of aposporous apomixis. The earliest phenotypic features of aposporous apomixis in this species are the mitotic formation of unreduced embryo sacs from a somatic cell of the ovule nucellus and the avoidance of meiosis. In this research we addressed gene expression variation in sexual and apomictic plants, by focusing on the ovule nucellus, which is the cellular domain primarily involved into the differentiation of meiocyte precursors and aposporous embryo sacs, at a pre-meiotic developmental stage. Gene expression analyses performed identified 396 DEGs and 1834 transcripts displaying phenotype-specific expression. Furthermore, the sequencing and assembly of the genome allowed the annotation of a 50kb sequence portion located upstream the HAPPY locus and to address the extent to which single transcripts were assembled in multiple variants . About one third of identified DEGs and phenotype-specific transcripts were associated to transcript variants with alternative expression patterns. Additionally, considering DEGs and phenotype-specific transcript, the co-expression level was estimated in about two transcripts per locus. Our gene expressiom study shows massive differences in the expression of several genes encoding for transposable elements. Transcriptional differences in the ovule nucellus and pistil terminal developmental stages were also found for a subset of genes encoding for potentially interacting proteins involved in pre-mRNA splicing. Furthermore, ovule transcriptomes were characterized by differential expression in genes operating in RNA silencing, RNA-mediated DNA methylation (RdDM) and histone and chromatin modifications. These findings are consistent with a role of these processes in regulating cell fate determination in the ovule, as indicated by forward genetic studies in sexual model species. The association between aposporous apomixis, pre-mRNA splicing and DNA methylation mediated by sRNAs, which is supported by expression data and by the enrichment in GO terms related to these processes, is consistent with the massive differential expression of multiple transposon-related sequences observed in ovules collected from both sexual and aposporous apomictic accessions. Overall, our data suggest that phenotypic expression of aposporous apomixis is concomitant with the modulation of key genes involved in the two interconnected processes: RNA splicing and RNA-directed DNA methylation.